2017
DOI: 10.5455/ijmsph.2017.0745302112016
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health status of construction workers: A review

Abstract: Industrialization plays a very important part in the economic development for a growing country with large population like India. Construction industry in India provides employment to about 40 million people. [1,2] However, construction work is one of the most hazardous sectors where health risks are significant due to dusts, noise, chemicals, manual handling, vibrating tools, excessive loads, and lack of safety awareness. [3] Higher rates of workplace injuries are reported among the illiterate and inexperienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 42 publications
1
32
0
2
Order By: Relevance
“…Adequate fluid intake and air circulation in the working places, thermal comfortability can be maintained during summer and monsoon seasons. [24] The present study has shown the occupational risk factors present in the unorganized textile yarn dyeing sectors despite having some limitations. The difficulty in obtaining a large number of samples from the study area imposes limits on the data interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate fluid intake and air circulation in the working places, thermal comfortability can be maintained during summer and monsoon seasons. [24] The present study has shown the occupational risk factors present in the unorganized textile yarn dyeing sectors despite having some limitations. The difficulty in obtaining a large number of samples from the study area imposes limits on the data interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Nowadays, work-related musculoskeletal disorders (WMSDs) are the most common occupational problem for both developing and developed countries, and it not only affects the workers' efficiency but at the same time it also affects their socioeconomic status as well as reduces productivity and increases the wage compensation cost while wasting millions of working hours. [3][4][5] Poor and awkward working postures are the main reasons behind these (MSDs) according to many scientists round the globe. [6,7] As most of the dyeing units are unorganized and under private entrepreneurship, workers of…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Lower back pain can be occurred due to repetitive forward bending and twisting of the back position which exerts compressive pressures on the lower vertebra and its surrounding back muscles. [33][34][35][36] The present study is also shown that 76% of workers are suffering from lower back pain due to prolong maintain of bent and twisted back postures.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] WMSDs are one of the most important causes for occupational hazards which not only affects the workers' efficiency and health conditions but also at the same time it decreases the production rates and waste millions of working hours. [5][6][7][8] Many researchers have reported about the strong association between awkward working postures and WMSDs [9][10][11][12][13][14][15] Several studies have also shown that some others factors such as age, education level, working experience, smoking, and alcohol consumption can also affect the musculoskeletal system of the workers. [16][17][18][19][20][21][22][23] Lack of preventive measures for risk factors, prolonged working hours, poor working environment, and socioeconomic status are responsible for the poor health conditions of the workers which in turn increases the psychological stresses and leads to workplace injuries.…”
Section: Introductionmentioning
confidence: 99%
“…The current rapid economic development has brought changes in workplaces in developing countries [3] and the organization of occupational health and safety services is not yet resilient enough to handle the growing demands for workers [4]. Construction hazards have received considerable attention over the last two decades [5].…”
Section: Literature Reviewmentioning
confidence: 99%